Contradictory links between lipid levels and bone health: atherogenic index of plasma and bone microarchitecture - Bo Xu; Guo-Liang Ma; Xin Chen; Bo-Wen Yang; Dian Zhang; Xiao-Kuan Qin; Tai-Wei Lou; Wei-Li Duan; Le Yu; Min-Shan Feng; He Yin; Xu Wei; et al. (Journal of Orthopaedic Surgery and Research)
Abstract Purpose Lipids increase osteoporosis and fracture risk, yet research on Atherogenic Index of Plasma (AIP), bone mineral density declines (BMD), and trabecular bone score (TBS) is limited. This study examined the relationships between AIP, TBS, and BMD in American adults using the National Health and Nutrition Examination Survey (NHANES) data, including the effect of obesity. Methods Based on data from 3,162 Americans, multivariable logistic regression and a generalized additive model (GAM) were used to analyze AIP, BMD, and TBS. Mediation studies assessed the impact of obesity (BMI) on these relationships. A threshold effect study identified turning points. Results The average participant age was 47.5 ± 17 years. AIP showed no correlation with BMD after BMI adjustment but was significantly associated with lumbar spine and femoral neck BMD without BMI adjustment. AIP negatively correlated with TBS even after adjusting for covariates. The relationship between AIP and TBS was L-shaped, with a turning point at -0.17. BMI mediated the AIP-BMD relationship by 122.01–131.49% (P < 0.05). Conclusions This study found AIP levels associated with decreased TBS and increased BMD, influenced by obesity. AIP may be a valuable tool in evaluating bone metabolism, indicating high BMD but poor TBS, warranting further exploration.